Left of boom : how a young CIA case officer penetrated the Taliban and Al-Qaeda - Laux, Douglas; Pezzullo, Ralph (St. Martin's Press, 2016)
"On September 11, 2001, Doug Laux was a freshman in college, on the path to becoming a doctor. But with the fall of the Twin Towers came a turning point in his life. After graduating he joined the Central Intelligence Agency, determined to get himself to Afghanistan and into the center of the action.